Correlation between religiosity, family functioning, and factors associated with substance use among secondary school students in high-risk areas. - Noor Adnin Ab Aziz; Suzaily Wahab; Rosnah Sutan; Muhammad Adib Baharom; Amirul Danial Azmi; Siti Azirah Asmai (PLoS ONE)
Introduction Substance use in adolescents poses a complex societal challenge, undermining nation-building and socioeconomic growth. Religiosity encompasses a person's religious beliefs, habits, and involvement in spiritual activities. Family functioning refers to a family unit's overall health and operation, including communication, emotional bonding, support, roles, and behavioral control. Both aspects are pivotal in determining substance use in adolescents. This study assesses the association between religiosity and family functioning and determines factors concerning substance use among adolescents in secondary schools in high-risk areas. Methods A cross-sectional study was conducted with 312 adolescents from selected secondary schools in substance use hotspot areas in Northern Malaysia. The tools used were Alcohol, Smoking, and Substance Involvement Screening Tool-Lite (ASSIST-Lite), Family Adaptation and Cohesion Scale version IV (FACES-IV), and Hatta Islamic Religiosity Scale (HIRS). Results The prevalence of substance use among adolescents was 9.6% (n = 30). Most users used a single substance (76.7%; n = 23), and only 23.3% (n = 7) used multiple substances. The mean age was 14.13 years (SD:0.67), the majority being Malays (99.0%; n = 309) with an Islamic background. Adolescent substance use was significantly associated with gender (16.3% in males and 6.3% in females, P = 0.004) and having a recent family history of substance use (16.8%, P = 0.003). No significant association between substance use and religiosity scores were elicited (W(1)=2.610, P = 0.106 and W(1)=0.092, P = 0.761 for knowledge and practices, respectively). However, substance use was found to be associated with family functioning subscales, which were chaotic family scores (W(1)=4.588, P = 0.032), and family satisfaction score (W(1)=4.831, P = 0.028). Regression analysis revealed that being male (Adj.OR=3.08, P = 0.006) and having a recent family history of substance use (Adj.OR=3.17, P = 0.004) significantly predicted substance use. Conclusions This study highlights the role of chaotic family dynamics and family satisfaction and its influence onto adolescent substance use. Despite the insignificant finding between religiosity and substance use, further exploration in this area is may prove beneficial to enhance care for individuals.